Colour perception in pathologists: the Farnsworth-Munsell 100-hue test. Issue 9 (September 1991) - Rigby, H S; Warren, B F; Diamond, J; Carter, C; Bradfield, J W
Abstract : The value of many histological stains depends on the ability of the observer to differentiate colour. This ability was assessed in 30 histopathologists and cytopathologists of varying experience using the Farnsworth-Munsell 100-hue test. As a group, the pathologists performed better than a reference population. Twenty eight subjects showed a wide ranging ability to differentiate colour: none was colour blind. Three of the 30 pathologists, however, fell below the twentieth centile for normal subjects and only one was aware of this deficiency! They may unknowingly misinterpret subtle stains. Two of these three had specific and major defects which could affect their ability to interpret a wide range of less subtle stains. Those with the poorest colour discrimination were not those with the least experience of microscopy. Pathologists should be apprised of the importance of their ability to discriminate colour, and that formal colour vision testing of prospective histopathologists may be appropriate.